OPTIMIZATION OF CULTURE CONDITIONS AND MEDIA COMPONENTS FOR LACCASE PRODUCTION USING WOOD ROTTING FUNGAL ISOLATE - PRIYANKA PUSHKARAJ VARTAK; DR. DEBJANI DASGUPTA (International Journal of Pharma and Bio Sciences, 2014)
The present work focuses on optimizing the culture conditions and media components for enhanced production of laccases using wood rotting fungal isolate. Parameters such as shaking or static conditions, agitation rate, pH and time for higher enzyme production were monitored. Medium for optimum laccase production was analysed using one factor at a time method and Taguchi orthogonal array method. One factor at a time method indicated that maltose, meat extract and ammonium sulphate were optimal carbon and nitrogen sources. 1% maltose, 0.750% meat extract, 0.124% ammonium sulphate (NH4)2SO4 and 0.1% potassium phosphate (KH2PO4) are found to be optimum concentrations for laccase production by Taguchi method. Under these optimized conditions laccase production increased by 49%. Enzyme production using various inducers showed that 2,6-xylidine was the most effective inducer.